Science and Other Poems - Deming, Alison Hawthorne, 1946- (Book collections on Project MUSE., 1994)
These poems imbue everything, from the microscopic to the stellar, with wonder. Each instant of illumination, like poetry itself, brings the world alive with "a faithfulness deeper than seeing."